The land of painted caves [compact disc, unabridged] - Auel, Jean M. (Auel, Jean M. Earth's children, 2010)
Ayla is training to become a Zelandoni, one of the community's spiritual leaders and healers. She becomes the acolyte to the Zelandoni for the Ninth Cave and begins the series of intensive journeys that are part of the sacred training. But as she struggles to find a balance between her calling and her duties as a new mother, her pursuits begin to take a toll on her relationship with Jondalar.